2021
DOI: 10.1111/1467-9566.13274
|View full text |Cite
|
Sign up to set email alerts
|

Platform encounters: A study of digitised patient follow‐up in HIV care

Abstract: Digital technologies are increasingly embedded in clinical encounters, reconfiguring the basis on which health care is delivered. Thereby, the delivery of care shifts from territorial locations in clinics and temporal modes of co‐presence towards digital platforms. Drawing on a sociotechnical evaluation of digitised patient follow‐up in HIV care, this paper argues that the forms of interactivity practised in platform encounters cannot be adequately understood through traditional interaction frameworks such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 43 publications
0
27
0
1
Order By: Relevance
“…Apart from changing the routine measurements of CD4 counts in stable PLHIV, the introduction of the Pathway also changed the way staff interacted with participants, which may have also resulted in cost changes. This was unfortunately not quantified during the study, but medical staff indicated that they were able to spend more time on PLHIV with more complex disease ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Apart from changing the routine measurements of CD4 counts in stable PLHIV, the introduction of the Pathway also changed the way staff interacted with participants, which may have also resulted in cost changes. This was unfortunately not quantified during the study, but medical staff indicated that they were able to spend more time on PLHIV with more complex disease ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Pathway was well received by users. When asked, most participants preferred to use the App at home and away from their work ( 32 ). This reduced the risk of disclosure and empowered them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our fifth paper, in this May issue, is Marent and Henwood's (2021) Platform encounters: A study of digitised patient follow‐up in HIV care , which keeps the focus on communication between HIV‐positive patients and their clinicians. As the authors note, service pressures from increasing populations with HIV and financial constraints have led healthcare providers, technology developers and other stakeholders to design and implement new digital platforms that can be offered alongside more traditional face‐to‐face consultations.…”
Section: Articles Included In This Special Sectionmentioning
confidence: 99%